On being me : a personal invitation to philosophy - Velleman, James David (Princeton University Press, 2020)
"In being me, a philosopher reflects in everyday language on what it is like to be a person, arriving at unexpected conclusions about the self and its future, time and mortality, free will and personal efficacy, regret and love. These topics are explored in brief sections titled "Wanting to go on", "Running out of time", "Regretting what might have been", "Aspiring to Authorship", "Making things happen", and "Wanting to be loved". Written in the first person, the text shows how reflecting on ordinary human concerns can lead anyone to profound puzzles that only philosophy can solve. Familiar examples and an artist's illustrations make each train of thought accessible to readers having no prior acquaintance with philosophy"--